KOS and Interoperability: challenges and trends within the ISKO International Conference (Advances in Knowledge Representation, 2022)
Interoperability refers to the ability of two or more systems to exchange information with each other. Amid the considerable amount of data in different formats available in digital environments, it is essential to adopt strategies so that available technological solutions can exchange information with minimum loss. In this sense, the use of Knowledge Organization Systems (KOS) has been increasingly important for the publication and retrieval of information on the web, as highlighted in the proposal of a Semantic Web. Therefore, this paper seeks to analyze the use of KOS to enable interoperability between systems and datasets on the web, with the objective of highlighting challenges and trends of the last decade related to this theme. The methodology adopted was an integrative literature review, using as corpus the articles published in the International Conference of the International Society for Knowledge Organization (ISKO) between 2012 and 2022. Keywords were defined for the search of the articles, resulting in a corpus of 158 documents to be evaluated. A textual analysis was carried out with citation of 57 studies that pointed out in their contents some trends in the use of KOS for enabling interoperability, as well as the challenges highlighted by the authors. As a conclusion, the possibilities of advancing this field of research and action are discussed.